Amides as modifiable directing groups in electrophilic borylation. Issue 14 (20th March 2023) - Iqbal, Saqib A.; Uzelac, Marina; Nawaz, Ismat; Wang, Zhongxing; Jones, T. Harri; Yuan, Kang; Millet, Clement R. P.; Nichol, Gary S.; Chotana, Ghayoor Abbas; Ingleson, Michael J.
Abstract : A sequence of amide-directed borylation followed by amide to amine reduction furnishes useful organoboranes that are otherwise convoluted to access. Abstract : Amide directed C–H borylation using ≥two equiv. of BBr3 forms borenium cations containing a R2 N(R′)CO→B(Ar)Br unit which has significant Lewis acidity at the carbonyl carbon. This enables reduction of the amide unit to an amine using hydrosilanes. This approach can be applied sequentially in a one-pot electrophilic borylation–reduction process, which for phenyl-acetylamides generates ortho borylated compounds that can be directly oxidised to the 2-(2-aminoethyl)-phenol. Other substrates amenable to the C–H borylation–reduction sequence include mono and diamino-arenes and carbazoles. This represents a simple method to make borylated molecules that would be convoluted to access otherwise ( e.g. N -octyl-1-BPin-carbazole). Substituent variation is tolerated at boron as well as in the amide unit, with diarylborenium cations also amenable to reduction. This enables a double C–H borylation–reduction–hydrolysis sequence to access B, N-polycyclic aromatic hydrocarbons (PAHs), including an example where both the boron and nitrogen centres contain functionalisable handles (N–H and B–OH). This method is therefore a useful addition to the metal-free borylation toolbox for accessing useful intermediates (ArylBPin) and novel B, N-PAHs.